Testifying in Court : Guidelines and Maxims for the Expert Witness - Brodsky, Stanley L., 1939- (American Psychological Association, 2013)
"Testifying in court can be a challenging experience. Novices who are unfamiliar with the judicial environment can feel insecure about many aspects of their testimony, from the language they use to the clothes they wear. Even experienced expert witnesses can be flustered by a skillful lawyer's cross-examination. For over 20 years, Stanley Brodsky's Testifying in Court has been a trusted guide for expert witnesses across a variety of professions. Readers have come to know and trust his sage and good-humored advice on every aspect of the experience from initial preparations to maintaining power and control during cross-examination. In this extensively updated edition of his classic text, the author has combined a wealth of new research with feedback from users of the first edition and his own evolving experience as an expert witness. As in the first edition, key principles are addressed in brief essays that draw on real-life scenarios and end in a take-home maxim"--Publicity materials. (PsycINFO Database Record (c) 2012 APA, all rights reserved).